How do you solve #y = 2x + 3# and #y = 3x + 1# using substitution?

1 Answer
Apr 16, 2017

Answer:

#x=2# and #y=7#

Explanation:

Sibstitution method involves getting value of one variable from one equation in terms of other variable and putting this in second equation to eliminate and find value of other variable.

Here we have #y=2x+3# in first equation and putting this in second equation, we get

#2x+3=3x+1#

or #2x-3x=1-3#

or #-x=-2#

i.e. #x=2#

Putting this Vale of #x# back in first equation, we get

#y=2×2+3=7#

Hence we get #x=2# and #y=7#